Ijtihad Ibn Qayyim Al-Jawziyyah dan al-Maqāṣid al-Juz’iyyah: Refleksi Penyelesaian Kasus Hukum Islam - nofialdi, Nofialdi (Fakultas Syariah IAIN Purwokerto, 2018)
The understanding of a mujtahid toward maqÄá¹£id al-syariÌ„Ê»ah becomes something urgent and significant, since ijtihad must be able to realize benefits, which is the substance of maqÄá¹£id al-syariÌ„Ê»ah both in the general scale (â€˜Ämmah), special (khÄá¹£á¹£ah), as well as in scale for specific cases (juz`iyyah). Ibn Qayyim, for example, in most cases is very concerned about maqÄá¹£id al-syariÌ„'ah, which one of its parts is al-maqÄá¹£id al-juzâ€™iyyah. In the case of the necessity of cleaning urine trails, specifically (juz'Ä«) it is not required to the urine of baby boys. This clearly shows that Ibn Qayyim is very concerned about al-maqÄá¹£id al-juzâ€™iyyah, because it is difficult to clean urine traces of baby boys so that it is not required to clean it up but simply by splashing water on the traces. Likewise in other cases, such as the necessity of ablution after eating camel meat, which is not required to be other than camel meat, the sale and purchase of salam (order) and the waiting period of women left behind, also shows that Ibn Qayyim is very concerned with the realization of al-maqÄá¹£id al-juzâ€™iyyah in establishing the law .